PARG suppresses tumorigenesis and downregulates genes controlling angiogenesis, inflammatory response, and immune cell recruitment - Sarah Johnson (BMC Cancer, 2022)
Abstract Chemokines are highly expressed in tumor microenvironment and play a critical role in all aspects of tumorigenesis, including the recruitment of tumor-promoting immune cells, activation of cancer-associated fibroblasts, angiogenesis, metastasis, and growth. Poly (ADP-ribose) polymerase (PARP) is a multi-target transcription regulator with high levels of poly(ADP-ribose) (pADPr) being reported in a variety of cancers. Furthermore, poly (ADP-ribose) glycohydrolase (PARG), an enzyme that degrades pADPr, has been reported to be downregulated in tumor tissues with abnormally high levels of pADPr. In conjunction to this, we have recently reported that the reduction of pADPr, by either pharmacological inhibition of PARP or PARG’s overexpression, disrupts renal carcinoma cell malignancy in vitro. Here, we use 3 T3 mouse embryonic fibroblasts, a universal model for malignant transformation, to follow the effect of PARG upregulation on cells’ tumorigenicity in vivo. We found that the overexpression of PARG in mouse allografts produces significantly smaller tumors with a delay in tumor onset. As downregulation of PARG has also been implicated in promoting the activation of pro-inflammatory genes, we also followed the gene expression profile of PARG-overexpressing 3 T3 cells using RNA-seq approach and observed that chemokine transcripts are significantly reduced in those cells. Our data suggest that the upregulation of PARG may be potentially useful for the tumor growth inhibition in cancer treatment and as anti-inflammatory intervention.